Anatomical investigations on the ossified tendons of the shank muscles in bronze turkey - Hasan Erden (Eurasian Journal of Veterinary Sciences)
In this study, the localizations of the ossified I tendons of the shank muscles were macroanatomically investigated in Bronze turkey. For this purpose, ten adult turkey were used. In this study, four on the origo tendons and fourteen on the insertio tendons, totally eighteen ossified regions were determined in each shank. In addition, it has been also found that all tendons of the muscles located in tarsometatarsal region were to be ossified.